DAMPAK PSIKOLOGIS PADA KEHAMILAN REMAJA (STUDI EKPLORASI DI DESA WATUTULIS PRAMBON SIDOARJO): PSYCHOLOGICAL IMPACT ON PREGNANCY ADOLESCENTS (EXPLORATION STUDY IN WATUTULIS VILLAGE PRAMBON SIDOARJO) - Hanum, Sri Mukhodim Faridah (Jurnal Kebidanan Midwiferia, 2015)
Married aged woman should be at least 21-22 years of age to be physically and psychologically.In the village watutulis Prambon-sidoarjo many women who already face teenage pregnancy. Of the total number of pregnant women in the ANC midwife are pregnant teenage mothers as much as 2.7% in 2005, 3.7% in 2006, 4.8% in 2007, 2.9% in 2008, 3 % in 2009, 6.4% in 2010. From the above data it can be concluded there was an increase of pregnant women who were aged early / adolescents each year, it can examine the impact that caused the individual psychologically as a result of a teenage pregnancy. The purpose of this study explores the psychological impact pregnant teenagers to receive pregnancy.The research method using qualitative research. Collecting data using primary and secondary data and then conducted in-depth interviews (depth interview), respondents were three people drawn from the data midwife and that have the same characteristics, namely the age of 15-19 years and who rarely ANC. The collected data are reported or verified and presented in a descriptive picture associated with the theory.The result showedteenagersexperiencing psychological disorders are like stress, depression, cease not to continue his education and abuse in infants.Concluded that there psychological stress, depression, persecution of a baby, do not stop to go to school in pregnant women in their teens in accepting her pregnancy. Based on these studies need to be done further research how far the psychological disturbances experienced by pregnant women who were aged teenagers.